Przeciwdziałanie skutkom katastrof naturalnych w regionie Azji Południowo-Wschodniej - Piepiora, Zbigniew (Counteracting the results of natural disasters in the region of Southeast Asia, 2009)
According to various sources the number of natural disasters increases in the region of Southeast Asia. Their occurrence often causes death or health injuries of many people and as a result - the decreasing quality of life in the region. In the face of these worrying facts it is necessary to make the analysis of this kind of phenomena and counteracting their results and this is the aim of this article
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 67, s. 232-245